Stable and durable super-hydrophobic fabric and preparation method thereof

Through the impregnation method of forming micro-nano rough structures on the fabric, the problems of complex preparation process and poor durability of existing superhydrophobic fabrics are solved, and low-cost and efficient preparation of superhydrophobic fabrics are achieved, with excellent chemical stability and mechanical durability. Suitable for oil-water separation technology.

CN119221290APending Publication Date: 2024-12-31HENAN UNIV OF URBAN CONSTR
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411510532.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing superhydrophobic fabrics have cumbersome preparation processes, harsh reaction conditions and poor durability, which limits their application in oil-water separation technology.

Method used

Using a simple impregnation method, the fabric is immersed in the polydimethylsiloxane solution, and sodium hydroxide, ammonium persulfate and copper chloride solutions are added. The micro-nano rough structure is formed by stirring at room temperature to obtain stable and durable superhydrophobic fabric. .

Benefits of technology

It realizes low-cost, environmentally friendly and efficient superhydrophobic fabric preparation, with excellent chemical stability and mechanical durability, can maintain superhydrophobicity for a long time, and shows good self-cleaning performance and oil-water separation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005105329480000011
    Figure HDA0005105329480000011
  • Figure HDA0005105329480000012
    Figure HDA0005105329480000012
  • Figure HDA0005105329480000021
    Figure HDA0005105329480000021
Patent Text Reader

Abstract

The invention belongs to the technical field of super-hydrophobic materials. The invention provides a preparation method of a stable and durable super-hydrophobic fabric. The method comprises the following steps: S1, immersing a fabric into an n-hexane solution of polydimethylsiloxane, and stirring; s2, adding a mixed solution of a sodium hydroxide solution and an ammonium persulfate solution into the solution with the fabric, and stirring; s3, continuously adding a copper chloride solution and stirring; s4, the fabric is taken out, washed and dried, and the stable and durable super-hydrophobic fabric is obtained. The prepared super-hydrophobic fabric not only has self-cleaning property, but also has excellent chemical stability and mechanical durability, and can keep super-hydrophobicity for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of super hydrophobic materials, and in particular relates to a stable and durable super hydrophobic fabric and a preparation method thereof. Background Art

[0002] In recent years, frequent crude oil spills and large-scale discharges of industrial oily wastewater have caused water pollution problems to become increasingly serious. Therefore, it is urgent to develop simple and efficient oily wastewater treatment technologies to cope with the increasingly severe challenges of water pollution. Among various oily wastewater treatment technologies, materials with superhydrophobic properties have attracted widespread attention because of their great potential application value in corrosion resistance, anti-icing, antibacterial, self-cleaning, and oil-water separation. The main feature of the surface of superhydrophobic materials is that they have a high water contact angle, which makes it almost impossible for water droplets to wet on their surface and thus slide off quickly. This superhydrophobicity is usually accompanied by superoleophilicity, which allows the material to selectively adsorb or filter oil from an oil-water mixture to achieve efficient oil-water separation. Therefore, giving porous materials superhydrophobic and superoleophilic properties is a very promising oil-water separation technology.

[0003] The performance of the surface of super-hydrophobic materials mainly depends on their microscopic geometric structure and chemical composition. Studies have shown that constructing a micro-nano rough structure on the surface of the substrate material and modifying it with a low surface energy substance can significantly improve the super-hydrophobicity of the material. Based on this theory, researchers have proposed a variety of methods for preparing super-hydrophobic surfaces, including hydrothermal method, sol-gel method, electrodeposition, electrospinning technology, layer-by-layer self-assembly, etching method, spraying, solution immersion method, etc. However, these preparation methods often involve complex special equipment, expensive and toxic fluorine-containing reagents, long preparation cycles and demanding environmental conditions. These difficulties not only limit the widespread application of super-hydrophobic materials, but also increase economic costs and environmental risks in actual production. In addition, super-hydrophobic coatings are usually damaged by mechanical forces or chemical corrosion in practical applications, and how to solve the durability of super-hydrophobic coatings remains a major challenge.

[0004] Therefore, it is particularly urgent in the field of oil-water separation technology to develop a super-hydrophobic cotton fabric that is simple and efficient, low-cost, environmentally friendly, can be mass-produced, has stable performance, and can be used for a long time. Summary of the invention

[0005] The present invention aims to solve the problems in the prior art such as complicated preparation process, harsh reaction conditions and poor durability of super hydrophobic fabrics, and provides a super hydrophobic fabric and a preparation method thereof which are simple to operate, low in cost, environmentally friendly and highly stable. The obtained fabric not only has self-cleaning properties, but also has excellent chemical stability and mechanical durability, and can maintain super hydrophobicity for a long time.

[0006] The technical solution adopted by the present invention to solve the above problems is as follows:

[0007] A method for preparing a stable and durable super-hydrophobic fabric comprises the following steps:

[0008] S1. Immerse the fabric in a hexane solution of polydimethylsiloxane and stir;

[0009] S2. Add a mixture of sodium hydroxide solution and ammonium persulfate solution to the solution containing the fabric and stir;

[0010] S3. Continue to add copper chloride solution and stir;

[0011] S4. Take out the fabric, rinse and dry it to obtain a stable and durable super-hydrophobic fabric.

[0012] Further, the fabric is a natural fiber fabric, a synthetic fiber fabric or a blended fiber fabric, for example, cotton fabric, wool fabric, polyester fabric, acrylic fabric, polyurethane fabric, nylon fabric, cotton-polyester blended fabric, cotton-polyester fabric, etc.

[0013] Preferably, the fabric is cotton fabric.

[0014] Furthermore, the fabric is washed and dried before the immersion.

[0015] Furthermore, in the n-hexane solution of polydimethylsiloxane, the mass fraction of the polydimethylsiloxane is 1.0 to 3.0 wt %.

[0016] Furthermore, the mass ratio of the curing agent to the polydimethylsiloxane is 1:10.

[0017] Furthermore, the concentration of the sodium hydroxide solution is 1.88-3.13 mol / L.

[0018] Preferably, the concentration of the sodium hydroxide solution is 2.5 mol / L.

[0019] Furthermore, the concentration of the ammonium persulfate solution is 0.08-0.13 mol / L.

[0020] Preferably, the concentration of the ammonium persulfate solution is 0.1 mol / L.

[0021] Furthermore, the concentration of the cupric chloride solution is 1.10-1.85 mol / L.

[0022] Preferably, the concentration of the cupric chloride solution is 1.5 mol / L.

[0023] Furthermore, in the process of preparing the stable and durable super-hydrophobic fabric, the volume ratio of the n-hexane solution of polydimethylsiloxane, the sodium hydroxide solution, the ammonium persulfate solution and the cupric chloride solution is 3 to 6:2 to 3:2:1.

[0024] Preferably, in the process of preparing the stable and durable super-hydrophobic fabric, the volume ratio of the n-hexane solution of polydimethylsiloxane, the sodium hydroxide solution, the ammonium persulfate solution and the cupric chloride solution added is 4:2:2:1.

[0025] Furthermore, the stirring time is 10 to 50 minutes.

[0026] Furthermore, the rinsing is performed by sequentially rinsing with ethanol and deionized water.

[0027] The present invention also provides a stable and durable super hydrophobic fabric prepared by the preparation method of the present invention.

[0028] The present invention has the following beneficial effects:

[0029] The present invention provides a method for preparing a stable and durable super-hydrophobic fabric, wherein a micro-nano rough structure is introduced on the surface of fabric fibers by a simple impregnation method and a lower surface energy is obtained, thereby obtaining a super-hydrophobic cotton fabric. The preparation method provided by the present invention is simple, easy to operate and environmentally friendly, the required reaction only needs to be carried out at room temperature, no high temperature conditions are required, no special equipment or strict preparation requirements are required, and the cost is low and no secondary pollution is generated, and the surface of the super-hydrophobic cotton fabric obtained thereby not only has good self-cleaning properties, but also has excellent chemical stability and mechanical durability, and can maintain super-hydrophobicity for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the SEM image of the cotton fabric after washing and drying;

[0031] Figure 2 The SEM image of the super hydrophobic cotton fabric provided in Example 1 of the present invention;

[0032] Figure 3 A surface state diagram of a water droplet dyed with methylene blue on the super-hydrophobic cotton fabric provided in Example 1;

[0033] Figure 4 This is a test diagram of the contact angle between the super-hydrophobic cotton fabric provided in Example 1 and deionized water;

[0034] Figure 5 A process diagram of a self-cleaning test of the super-hydrophobic cotton fabric provided in Example 1;

[0035] Figure 6A graph showing the change in water contact angle of the super-hydrophobic cotton fabric provided in Example 1 after 200 friction cycles;

[0036] Figure 7 This is a graph showing the change in water contact angle of the super-hydrophobic cotton fabric provided in Example 1 after washing for 120 minutes;

[0037] Figure 8 A graph showing the change in water contact angle of the super-hydrophobic cotton fabric provided in Example 1 after ultrasonic treatment for 60 minutes;

[0038] Fig. 9 A graph showing the change in water contact angle of the super-hydrophobic cotton fabric provided in Example 1 after 5 days of ultraviolet irradiation;

[0039] Fig.10 A process diagram of removing n-hexane from the water surface light oil from the super-hydrophobic cotton fabric provided in Example 1;

[0040] Fig.11 A process diagram of removing heavy oil dichloromethane from water using the super hydrophobic cotton fabric provided in Example 1;

[0041] Fig.12 A comparison chart of the separation efficiency of the super-hydrophobic cotton fabric provided in Example 1 for different types of oil-water mixtures;

[0042] Fig.13 A graph showing the change in the cyclic separation efficiency of a mixture of dichloromethane and water by the super-hydrophobic cotton fabric provided in Example 1;

[0043] Fig.14 A surface state diagram of a water droplet dyed with methylene blue on the super-hydrophobic cotton fabric provided in Comparative Example 1, and a contact angle test diagram of the super-hydrophobic cotton fabric provided in Comparative Example 1 and deionized water;

[0044] Fig.15 A graph showing the change in water contact angle of the super-hydrophobic cotton fabric provided in Comparative Example 1 after 200 friction cycles;

[0045] Fig.16 The water contact angle change diagram of the super hydrophobic cotton fabric provided in Comparative Example 1 after washing for 120 minutes;

[0046] Fig.17 The water contact angle change diagram of the super hydrophobic cotton fabric provided in Comparative Example 1 after ultrasonic treatment for 60 minutes;

[0047] Fig.18 This is a graph showing the change in water contact angle of the superhydrophobic cotton fabric provided in Comparative Example 1 after 5 days of ultraviolet irradiation. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments, and are not limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] The cotton fabrics used in the following examples and comparative examples were first washed and dried, specifically including: washing the cotton fabrics with ethanol and deionized water in sequence to remove pollutants on the surface of the cotton fabrics, and then drying them in an oven at 60° C. for later use.

[0050] The n-hexane solution of polydimethylsiloxane used in the following examples and comparative examples was prepared, wherein the specific preparation method of the n-hexane solution of polydimethylsiloxane with a mass fraction of 1.0wt% comprises: dissolving 0.4g of polydimethylsiloxane and 0.04g of curing agent in 60mL of n-hexane to obtain the n-hexane solution of polydimethylsiloxane. The preparation methods of n-hexane solutions of polydimethylsiloxane with other mass fractions can be obtained in the same way.

[0051] Example 1

[0052] S1. The washed and dried cotton fabric was immersed in 20 mL of n-hexane solution of polydimethylsiloxane (mass fraction: 1.0 wt%) and stirred for 10 min;

[0053] S2. Add a mixture of 10 mL of sodium hydroxide solution (2.5 mol / L) and 10 mL of ammonium persulfate solution (0.1 mol / L) to the solution containing the cotton fabric and stir for 10 min;

[0054] S3. Continue to add 5 mL of copper chloride aqueous solution (1.5 mol / L) and stir for 30 min;

[0055] S4. Take out the cotton fabric, rinse it with ethanol and deionized water in turn, and then place it in an oven at 80°C to dry it to obtain a stable and durable superhydrophobic cotton fabric.

[0056] The super hydrophobic cotton fabric obtained in Example 1 was tested, and the results are shown in Figure 2 to Figure 13 .

[0057] Figure 1 This is the SEM image of cotton fabric after washing and drying. Figure 1 It can be seen that the cotton fabric after washing and drying is composed of fibers, and the fiber surface is relatively smooth.

[0058] Figure 2The SEM image of the super hydrophobic cotton fabric provided in Example 1 of the present invention. Figure 2 It can be seen that the surface of the cotton fiber becomes very rough, and a large number of micro-nano structures are evenly accumulated on the fiber surface to form a rough structure.

[0059] Figure 3 The surface state diagram of the super hydrophobic cotton fabric provided in Example 1 is a water droplet dyed with methylene blue. Figure 3 It can be seen that the water drop placed on the surface of the super-hydrophobic cotton fabric of Example 1 is spherical;

[0060] Figure 4 This is a test diagram of the contact angle between the super-hydrophobic cotton fabric and deionized water provided in Example 1. The water contact angle on the surface of the super-hydrophobic cotton fabric in Example 1 is 154.6±1.2°, and the rolling angle is about 6°.

[0061] Figure 5 This is a process diagram of the self-cleaning test of the super-hydrophobic cotton fabric provided in Example 1. The self-cleaning test uses chalk powder as a pollutant to evaluate the self-cleaning ability of the cotton fabric. Figure 5 As shown, during the self-cleaning test, the cotton fabric was adhered to a glass slide with tape and the surface was covered with chalk powder. It was placed tilted in a culture dish, and then a syringe was used to provide a certain amount of water flow to clean the surface of the super-hydrophobic cotton fabric in Example 1. It can be seen that the water flow jumped off the surface of the cotton fabric, taking away the chalk powder at the same time, leaving a clean surface. This shows that the surface of the super-hydrophobic cotton fabric prepared in Example 1 has excellent waterproof performance and good self-cleaning performance, and can prevent the surface from being contaminated.

[0062] Figure 6 The water contact angle change diagram of the super hydrophobic cotton fabric provided in Example 1 after 200 friction cycles. The friction cycle test method includes: laying the cotton fabric flat on 800-grit sandpaper, then placing a 200g weight on the cotton fabric, and pulling it in one direction for 10cm at a speed of 10cm / s, which is defined as one friction cycle. Figure 6 As shown, with the increase of the number of frictions, the water contact angle on the surface of the super-hydrophobic cotton fabric of Example 1 gradually decreases, but it still has super-hydrophobicity after 200 friction cycles, and the water contact angle on its surface still remains above 150°.

[0063] Figure 7 The water contact angle change diagram of the super hydrophobic cotton fabric provided in Example 1 after washing for 120 minutes. The washing test method includes: soaking the cotton fabric in an aqueous solution containing 1wt% detergent and washing it at room temperature at a stirring speed of 500rpm. Figure 7 As shown, after 120 minutes of washing test, the water contact angle of the surface of the super hydrophobic cotton fabric of Example 1 is 152.8±1.3°.

[0064] Figure 8 The water contact angle change diagram of the super-hydrophobic cotton fabric ultrasonically treated for 60 minutes provided in Example 1. The method of ultrasonic treatment test includes: sticking the cotton fabric on a glass slide with tape and placing it in a beaker filled with deionized water, and then placing the beaker in an ultrasonic cleaner (CR-030S, 180W, 40kHz). Figure 8 As shown, after the super-hydrophobic cotton fabric of Example 1 was subjected to 60 minutes of ultrasonic treatment, the water contact angle on its surface was 153.4±1°.

[0065] Fig. 9 The water contact angle change diagram of the super hydrophobic cotton fabric provided in Example 1 after ultraviolet irradiation for 5 days. The method of ultraviolet irradiation test includes: exposing the cotton fabric to an ultraviolet lamp (40W, irradiation distance: 15cm). Fig. 9 As shown, after the super-hydrophobic cotton fabric of Example 1 was irradiated with ultraviolet light for 5 days, the water contact angle on its surface was 153.7±1.4°.

[0066] Fig.10 This is a process diagram of removing n-hexane from the water surface from the super-hydrophobic cotton fabric provided in Example 1. Fig.10 As shown, the super-hydrophobic cotton fabric provided in Example 1 can actively absorb light oil n-hexane (Sudan III dyeing) on ​​the water surface.

[0067] Fig.11 This is a process diagram of the super hydrophobic cotton fabric provided in Example 1 removing heavy oil dichloromethane from water. Fig.11 As shown, the super-hydrophobic cotton fabric provided in Example 1 can actively absorb the heavy oil dichloromethane (Sudan III dyeing) under water.

[0068] Fig.10 and Fig.11 The experimental results show that the super-hydrophobic cotton fabric provided in Example 1 has good super-hydrophobic and super-oleophilic properties.

[0069] Fig.12 The following is a comparison chart of the separation efficiency of the super-hydrophobic cotton fabric provided in Example 1 for different types of oil-water mixtures. The specific method of the separation efficiency test includes: using a clamp to fix a piece of the super-hydrophobic cotton fabric provided in Example 1 between two glass tubes, and then pouring a mixture of 20mL of dichloromethane and 20mL of deionized water into the homemade separation device for oil-water separation test. Due to the super-lipophilicity of the prepared cotton fabric, dichloromethane quickly penetrates through the fabric under the action of gravity and is collected in a glass container placed under the separation device, while due to the super-hydrophobicity of the prepared cotton fabric, water is trapped in the upper glass tube. Similarly, several other types of oil-water mixtures (n-hexane, xylene, cyclohexane, chloroform) are separated and tested as above. Fig.12As shown, the separation efficiency of the super hydrophobic cotton fabric in Example 1 for these types of oil-water mixtures (n-hexane, xylene, cyclohexane, dichloromethane, chloroform) is more than 98%.

[0070] Fig.13 The graph of the change of the cyclic separation efficiency of the super hydrophobic cotton fabric for the mixture of dichloromethane and water provided in Example 1. The specific method of the cyclic separation test includes: using a mixture of dichloromethane and deionized water to test the cyclic use ability of the cotton fabric prepared in this example, washing the cotton fabric contaminated by dichloromethane after separation with ethanol and deionized water in turn, drying at room temperature, and then performing the next cyclic separation. Fig.13 It can be seen that after the super-hydrophobic cotton fabric provided in Example 1 cyclically separated the mixture of dichloromethane and water for 100 times, the super-hydrophobic cotton fabric provided in Example 1 still exceeded 97%. This result well proves that the super-hydrophobic cotton fabric has good stability and strong recycling ability, and has excellent oil-water separation efficiency.

[0071] Example 2

[0072] S1. The washed and dried cotton fabric was immersed in 15 mL of n-hexane solution of polydimethylsiloxane (mass fraction: 2.0 wt%) and stirred for 10 min;

[0073] S2. Add a mixture of 15 mL of sodium hydroxide solution (1.88 mol / L) and 10 mL of ammonium persulfate solution (0.08 mol / L) to the solution containing the cotton fabric and stir for 10 min;

[0074] S3. Continue to add 5 mL of copper chloride aqueous solution (1.10 mol / L) and stir for 30 min;

[0075] S4. Take out the cotton fabric, rinse it with ethanol and deionized water in turn, and then place it in an oven at 80°C to dry it to obtain a stable and durable superhydrophobic cotton fabric.

[0076] The super-hydrophobic cotton fabric prepared in Example 2 was tested. The water contact angle on the surface of the super-hydrophobic cotton fabric in Example 2 was 153.8±0.9°, and the rolling angle was about 8°.

[0077] Example 3

[0078] S1. The washed and dried cotton fabric was immersed in 30 mL of n-hexane solution of polydimethylsiloxane (mass fraction: 2.0 wt%) and stirred for 10 min;

[0079] S2. Add a mixture of 10 mL of sodium hydroxide solution (3.13 mol / L) and 10 mL of ammonium persulfate solution (0.13 mol / L) to the solution containing the cotton fabric and stir for 10 min;

[0080] S3. Continue to add 5 mL of copper chloride aqueous solution (1.85 mol / L) and stir for 30 min;

[0081] S4. Take out the cotton fabric, rinse it with ethanol and deionized water in turn, and then place it in an oven at 80°C to dry it to obtain a stable and durable superhydrophobic cotton fabric.

[0082] The super-hydrophobic cotton fabric prepared in Example 3 was tested. The water contact angle on the surface of the super-hydrophobic cotton fabric in Example 3 was 154±1.3°, and the rolling angle was about 7°.

[0083] Example 4

[0084] S1. Take 20 mL of n-hexane solution of polydimethylsiloxane (mass fraction 3.0 wt%) and stir for 10 min;

[0085] S2. Add 15 mL of sodium hydroxide solution (2.5 mol / L) and 10 mL of ammonium persulfate solution (0.1 mol / L) to the n-hexane solution of polydimethylsiloxane in step S1 and stir for 10 min to obtain a mixed solution;

[0086] S3. Add 5 mL of copper chloride aqueous solution (1.5 mol / L) to the mixed solution of step S2, immerse the washed and dried cotton fabric in it and stir for 30 min;

[0087] S4. Take out the cotton fabric, rinse it with ethanol and deionized water in sequence, and then dry it in an oven at 80° C. to obtain a superhydrophobic cotton fabric.

[0088] The super-hydrophobic cotton fabric prepared in Example 4 was tested. The water contact angle on the surface of the super-hydrophobic cotton fabric in Example 4 was 152.1±1.2°, and the rolling angle was about 10°.

[0089] Comparative Example 1

[0090] S1. Immerse the washed and dried cotton fabric in 20 mL of n-hexane solution of polydimethylsiloxane (mass fraction: 1.0 wt%);

[0091] S2. Add a mixture of 10 mL of sodium hydroxide solution (2.5 mol / L) and 10 mL of ammonium persulfate solution (0.1 mol / L) to the solution containing the cotton fabric;

[0092] S3. Continue to add 5 mL of copper chloride aqueous solution (1.5 mol / L) and stir for 5 min;

[0093] S4. After standing still for 30 minutes, the cotton fabric was taken out, rinsed with ethanol and deionized water in turn, and then placed in an oven at 80°C to dry to obtain a superhydrophobic cotton fabric.

[0094] The super hydrophobic cotton fabric obtained in the comparative example was tested, and the results are shown in Figures 14 to 18 .

[0095] Fig.14 The following are the surface state diagrams of water droplets dyed with methylene blue on the super-hydrophobic cotton fabric provided in Comparative Example 1, and the contact angle test diagrams of the super-hydrophobic cotton fabric provided in Comparative Example 1 and deionized water. Fig.14 It can be seen that the water drop placed on the surface of the super-hydrophobic cotton fabric of Comparative Example 1 is spherical, and the water contact angle on the surface of the super-hydrophobic cotton fabric of Comparative Example 1 is 151.5±1.1°. This shows that the super-hydrophobic cotton fabric of Comparative Example 1 has super-hydrophobic properties, but the material distribution on its surface is very uneven.

[0096] Fig.15 The water contact angle change diagram of the super hydrophobic cotton fabric provided in Comparative Example 1 after 200 friction cycles. Fig.15 As shown, after 200 friction cycles, the water contact angle on the surface of the superhydrophobic cotton fabric of Comparative Example 1 is 142.1±1.5°.

[0097] Fig.16 The water contact angle change diagram of the super hydrophobic cotton fabric provided in Comparative Example 1 after washing for 120 minutes. Fig.16 As shown, after 120 minutes of washing test, the water contact angle of the surface of the super hydrophobic cotton fabric of Comparative Example 1 is 142.9±1°.

[0098] Fig.17 The water contact angle change diagram of the super hydrophobic cotton fabric provided in Comparative Example 1 after ultrasonic treatment for 60 minutes. Fig.17 As shown, after the super-hydrophobic cotton fabric of Comparative Example 1 was subjected to 60 minutes of ultrasonic treatment, the water contact angle on its surface was 141.5±1.6°.

[0099] Fig.18 The water contact angle change diagram of the super hydrophobic cotton fabric provided in Comparative Example 1 after ultraviolet irradiation for 5 days. Fig.18 As shown, after the super-hydrophobic cotton fabric of Comparative Example 1 was irradiated with ultraviolet light for 5 days, the water contact angle on its surface was 139.2±1.3°.

[0100] From the test results of the above embodiments and comparative examples, it can be seen that the super-hydrophobic cotton fabric provided in Example 1 of the present invention has better chemical stability and mechanical durability than the super-hydrophobic cotton fabric provided in Comparative Example 1. The super-hydrophobic cotton fabric provided in Example 1 has significantly smaller changes in hydrophobicity after multiple washing and wear, and can maintain super-hydrophobicity for a long time.

[0101] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0102] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0103] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a stable and durable super-hydrophobic fabric, characterized in that: The following steps are involved: S1. Immerse the fabric in a hexane solution of polydimethylsiloxane and stir; S2. Add a mixture of sodium hydroxide solution and ammonium persulfate solution to the solution containing the fabric and stir; S3. Continue to add copper chloride solution and stir; S4. Take out the fabric, rinse and dry it to obtain a stable and durable super-hydrophobic fabric.

2. The method for preparing a stable and durable super-hydrophobic fabric according to claim 1, characterized in that: The fabric is a natural fiber fabric, a synthetic fiber fabric or a blended fiber fabric.

3. The method for preparing a stable and durable super-hydrophobic fabric according to claim 1, characterized in that: In the n-hexane solution of polydimethylsiloxane, the mass fraction of the polydimethylsiloxane is 1.0-3.0 wt %.

4. The method for preparing a stable and durable super-hydrophobic fabric according to claim 1, characterized in that: The n-hexane solution of polydimethylsiloxane further contains a curing agent, and the mass ratio of the curing agent to the polydimethylsiloxane is 1:

10.

5. The method for preparing a stable and durable super-hydrophobic fabric according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 1.88-3.13 mol / L.

6. The method for preparing a stable and durable super-hydrophobic fabric according to claim 1, characterized in that: The concentration of the ammonium persulfate solution is 0.08-0.13 mol / L.

7. The method for preparing a stable and durable super-hydrophobic fabric according to claim 1, characterized in that: The concentration of the cupric chloride solution is 1.10-1.85 mol / L.

8. The method for preparing a stable and durable super-hydrophobic fabric according to claim 1, characterized in that: In the process of preparing the stable and durable super-hydrophobic fabric, the volume ratio of the n-hexane solution of polydimethylsiloxane, the sodium hydroxide solution, the ammonium persulfate solution and the cupric chloride solution is 3 to 6:2 to 3:2:

1.

9. The method for preparing a stable and durable super-hydrophobic fabric according to claim 1, characterized in that: The stirring time is 10 to 50 minutes.

10. A stable and durable super hydrophobic fabric, characterized in that: Prepared by the preparation method according to any one of claims 1 to 9.